Application of fungal multienzyme extract for umbu juice clarification (Research, Society and Development, 2022)
The umbu (Spondias tuberosa Arruda), also known as imbu or ambu, is a fruit of the umbu tree, a natural fruit of the Brazilian semi-arid region, which belongs to the anacardiaceae family, whose genus is Spondias. the food, pharmaceutical and chemical industries. They can be used as catalysts, since they can accelerate the speed of reactions and can be applied during the production processes of various compounds, such as sensory determination and increased shelf life. This study aims to analyze whether the use of a fungal multienzyme extract in the preparation of umbu juice can hydrolyze pectin and other interferences, which alter the color and other organoleptic properties of the juice. The research has a qualitative approach, which aims to formulate relationships between determinable experimental characteristics, of an object of study or class of phenomena. The research took place in the laboratory of a college in the interior of Bahia, in the city of Vitória da Conquista. The results showed that the registered fungus Rhizopus oligosporus 011240290N was efficient in the production of polygalacturonase, being an alternative for the reuse of coffee agro-industrial waste. The results obtained are considered promising when compared with data from the literature, demonstrating that they can be used for juice clarification, and the enzyme showed excellent Ph, turbidity, density, total acidity and brix activities.